2002
DOI: 10.1108/09576050210436138
|View full text |Cite
|
Sign up to set email alerts
|

Information systems outsourcing: reasons, reservations and success factors

Abstract: The aim of this paper is to determine the main reasons that lead to information systems outsourcing, the reservations that are initially present in front of this kind of contract and the factors considered necessary for the success of outsourcing in the case of Spanish public universities. With this aim, a survey has been made among information systems managers in those universities. The results show the possibility of establishing a typology of universities depending on the position they have adopted with res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
9

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 46 publications
(54 reference statements)
4
40
0
9
Order By: Relevance
“…Further research using a wider study sample will need to be conducted in order for management lessons that emerge to be applicable across a wider business perspective. (2006) No available data from our research Outcomes of our study supports work conducted by Davidson and Olfman (2004), Millar and Audisio (2006) and Bi (2007) The outcome of our research supports work conducted by Yang and Huang (2000), Claver et al (2002b) and Millar and Audisio (2006) (continued) It is essential that formal structures in the area of change management are employed The customer and vendor relationship is of paramount importance and should evolve into an integrated team situation A high emphasis should be given to the backup of crucial systems and data at different sites Technology management…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Further research using a wider study sample will need to be conducted in order for management lessons that emerge to be applicable across a wider business perspective. (2006) No available data from our research Outcomes of our study supports work conducted by Davidson and Olfman (2004), Millar and Audisio (2006) and Bi (2007) The outcome of our research supports work conducted by Yang and Huang (2000), Claver et al (2002b) and Millar and Audisio (2006) (continued) It is essential that formal structures in the area of change management are employed The customer and vendor relationship is of paramount importance and should evolve into an integrated team situation A high emphasis should be given to the backup of crucial systems and data at different sites Technology management…”
Section: Discussionsupporting
confidence: 48%
“…The research shows a positive response in favour of the growing importance of quality of service requirements in ICT outsourcing projects (Yang and Huang, 2000;Claver et al, 2002b;Millar and Audisio, 2006): Lessons. In a similar way, to standard quality management approaches, any quality programme to be initiated for an ICT outsourcing project should include considerations of various factors. These factors include for example, ensuring the availability of standards (as relates to documents, processes, etc.…”
Section: Quality Managementmentioning
confidence: 99%
“…Many firms thus fear a Possible Opposition of their Staff to the outsourcing decision, which poses a threat to their job (Grover, Cheon and Teng, 1994;Claver et al, 2002;Brook, 2006), this being a risk that becomes even greater in the case of global outsourcing.…”
Section: Is Otsourcing Risksmentioning
confidence: 99%
“…This reason is closely related to the above-mentioned increase in IS management flexibility. It is undeniable that, thanks to outsourcing, a firm does not have to depend exclusively on its internal IS resources (Claver et al, 2002) Saving Technology Costs. Service providers are exposed to a wider variety of problems and experiences associated with IS, which is why a greater volume of knowledge and skills can be obtained that will help to solve these problems.…”
Section: Is Outsourcing Reasonsmentioning
confidence: 99%
“…Fernie (1999) have found that organizations outsource the 3PLs due to the expertise of contractors and their asset utilization on their business. Similarly, the significant drivers of outsourcing 3PL are cost saving and capital investment reduction (Embleton and Wright, 1998;Claver, Gonzales, Gasco & Llopis, 2002;Corbett, 1998;Razzaque and Sheng, 1998;Trunick, 1989). According to some researchers, outsourcing Third-Party Logistics leads toward the enhancement of business performance and processes (Clott, 2004;Embleton and Wright, 1998;Corbett, 1998).…”
Section: Reasons Of Outsourcing 3 Rd Party Logistics Service Providersmentioning
confidence: 99%